The Number of confirmed cases of covid-19 in ecuador, identified by province of attention, complies with the distribution of the newcomb-benford law - Jara-Ortega, Paul (2021)
Abstract Background: The epidemiological data of COVID-19, from China, the United States, South Korea, England, Spain, Italy, Germany, Holland and Sweden are adjusted to the distribution of the Newcomb-Benford Law (LNB), which would indicate that there is no falsification of data. there is no report made with epidemiological data from Ecuador. Objective: To know if the data provided by the Ministry of Public Health (MSP) of Ecuador, with respect to the confirmed cases with COVID-19 by province of care, are adjusted to LNB. Material and methods: The epidemiological database of the Ministry of Public Health of Ecuador was used, where the LNB was applied to the epidemiological data and then the Chi-Square test of goodness of fit was applied. Results: A p value of 0.872 was obtained, which is greater than the significance value α = 0.05 and a Chi-square value = 3.82722, which is less than the critical value of Chi-square 15.5073. Conclusion: The null hypothesis was accepted, assuming that the epidemiological data do conform to the LNB and therefore there would be no falsified data.